2011
DOI: 10.1016/j.yexcr.2011.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic signaling is required for fluid shear stress-induced NF-κB translocation in osteoblasts

Abstract: Fluid shear stress regulates gene expression in osteoblasts, in part by activation of the transcription factor NF-κB. We examined whether this process was under control of purinoceptor activation. MC3T3-E1 osteoblasts under static conditions expressed the NF-κB inhibitory protein IκBα and exhibited cytosolic localization of NF-κB. Under fluid shear stress, IκBα levels decreased, and concomitant nuclear localization of NF-κB was observed. Cells exposed to fluid shear stress in ATP-depleted medium exhibited no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 70 publications
1
17
0
Order By: Relevance
“…ATP is an important autocrine/paracrine signaling molecule released by osteoblasts and osteocytes in response to mechanical stimulation in vitro (15). Several studies have reported that activation of the purinergic receptors by ATP is required for NF-B translocation, ERK1/2 activation, Cox-2 expression, and PGE 2 release, all major anabolic factors for bone formation (13,14). Although translocation and redistribution of CAV1 have been reported with mechanical stretch in type II epithelial cells (48), our novel findings indicate that CAV1 is redistributed from the lipid microdomain fractions into the denser cytosolic fractions when MC3T3-E1 cells were stimulated with ATP.…”
Section: Discussionmentioning
confidence: 99%
“…ATP is an important autocrine/paracrine signaling molecule released by osteoblasts and osteocytes in response to mechanical stimulation in vitro (15). Several studies have reported that activation of the purinergic receptors by ATP is required for NF-B translocation, ERK1/2 activation, Cox-2 expression, and PGE 2 release, all major anabolic factors for bone formation (13,14). Although translocation and redistribution of CAV1 have been reported with mechanical stretch in type II epithelial cells (48), our novel findings indicate that CAV1 is redistributed from the lipid microdomain fractions into the denser cytosolic fractions when MC3T3-E1 cells were stimulated with ATP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ca 2C influx following P2X7R activation causes sustained proton efflux dependent on glucose and phosphatidylinositol 3-kinase activity (Grol et al 2012) and activation of PKC to mediate phosphorylation of ERK1/2 (Liu et al 2008, Okumura et al 2008, suggestive of more cross talk in osteoblast-like cells. A fluid sheer stress-induced NF-kB nuclear localisation independent of both ERK1/2 LPA signalling has also been demonstrated through P2X7R in osteoblasts (Genetos et al 2011). It seems likely that while the basal/transient activation of P2X7R is osteogenic, sustained stimulation could inhibit the function and activity of these bone-forming cells.…”
Section: Mature Cellsmentioning
confidence: 93%
“…In addition, blockade or absence of P2X7R has been shown to inhibit propagation of intercellular calcium signalling between osteoblasts and osteoclasts in human bone marrow-derived cells (Jorgensen et al 2002), significantly reduce ERK phosphorylation in response to fluid shear stress in mouse primary osteoblasts (Liu et al 2008, Okumura et al 2008) and prevented fluid shear-stress-induced IkBa degradation and nuclear accumulation of nuclear factor kappa B (NFkB) in MC3T3-E1 osteoblasts (Genetos et al 2011).…”
Section: Mature Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluid shear stress can also regulate gene expression in osteoblasts, in part by activation of the transcription factor NF-κB, through P2X7 and P2Y 6 receptors [213]. Brief activation of P2X7 receptors on MC3T3-E1 osteoblast-like cells has been shown to trigger a dramatic Ca 2+ -dependent stimulation of metabolic acid production [214].…”
Section: Functional Effects Of P2 Receptor-mediated Signalling In Ostmentioning
confidence: 99%